أثر المقتربات الخططية لمواقف اللعب الأكثر شيوعاً في أداء بعض المهارات الاساسية للناشئين بالكرة الطائرة - متعب, سامر يوسف; دوهان, علي عبد الكريم (Sulaimani Journal for Humanities, 2018)
The volleyball is one of the games, which has open environment, it require good player with high skills, and be able to perform it in different conditions due to the requirement of competition during the matches where the interfering in the perform skills, therefore the conditions of the practice and training must be similar. The problem of research was, the researcher notes weak in the performed of basic skills for junior players and there were differences between their performance levels when they performed singular and through the practice with match conditions. Therefore, the researchers decided to deal with this problem through the Conjugation approaches of most playing situations. The aims of study was knowledge the effect of Conjugation approaches in development perform some basic skills in volleyball, as well as design some new tests to measure some skill in situations similar the competition. Researchers used the excremental research by equal groups design. The sample research was junior players age (14-16) years at Al-hashimea club in Babylon city, compose of (24) players. The data analyzed by spss program and achieved for many conclusion was most important; there were significant differences for Conjugation approaches to develop the performance of skills.
Keywords: volleyball skills Conjugation approaches